Stakeholder workshop report: Women’s empowerment in agrifood systems governance (WEAGov) technical workshop: Nigeria pilot study - Kyle, Jordan; Ragasa, Catherine; Carrillo, Lucia (International Food Policy Research Institute, 2023)
Inclusive governance and policies can promote adaptation to climate change as well as resilience of women in the agrifood system. The Women's impowerment in Agrifood Governance (WEAGov) is a diagnostic tool developed by IFPRI to help evaluate the extent to which women are empowered across the policy cycle related to agrifood systems. WEAGov provides a way to identify gaps and opportunities to raise women’s voice and agency at different stages of the policy cycle, and provides a basis for monitoring progress in women’s empowerment in agrifood systems governance over time. The workshop described here took place on May 11, 2023 in Abuja, Nigeria and included policymakers, researchers, and private sector representatives. The workshop familiarized stakeholders with the WEAGov assessment framework and collected valuable inputs and feedback on a recent WEAGov pilot study conducted in Nigeria. While participants largely validated the WEAGov indicators, they recommended key areas for improved measurement which will be incorporated into the assessment framework.